2022
DOI: 10.1186/s12936-021-04023-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and anti-malarial drug resistance profile of Plasmodium falciparum from patients attending Kisoro Hospital, southwestern Uganda

Abstract: Background The evolution of malaria infection has necessitated the development of highly sensitive diagnostic assays, as well as the use of dried blood spots (DBS) as a potential source of deoxyribonucleic acid (DNA) yield for polymerase chain reaction (PCR) assays. This study identified the different Plasmodium species in malaria-positive patients, and the anti-malarial drug resistance profile for Plasmodium falciparum using DBS samples collected from patients attending Kisoro Hospital in Kiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
5
1
Order By: Relevance
“…A study conducted in four contagious villages in Mulanda subcounty in Tororo District, Eastern Uganda, showed that infection due to Plasmodium falciparum was 94.0%, which was also the most common species identified; Plasmodium malariae was 6.0%, and there were no mixed infections seen [45]. Similar studies conducted in selected health care facilities across Ghana and Kisoro Hospital in southwestern Uganda showed results that were not significantly different from our study, with the exception of P. malariae, which was not identified in our study [24,46]. Studies in the same region of Uganda show results that are not significantly different from our study results [47][48][49].…”
Section: The Most Common Plasmodium Speciescontrasting
confidence: 51%
“…A study conducted in four contagious villages in Mulanda subcounty in Tororo District, Eastern Uganda, showed that infection due to Plasmodium falciparum was 94.0%, which was also the most common species identified; Plasmodium malariae was 6.0%, and there were no mixed infections seen [45]. Similar studies conducted in selected health care facilities across Ghana and Kisoro Hospital in southwestern Uganda showed results that were not significantly different from our study, with the exception of P. malariae, which was not identified in our study [24,46]. Studies in the same region of Uganda show results that are not significantly different from our study results [47][48][49].…”
Section: The Most Common Plasmodium Speciescontrasting
confidence: 51%
“…Evaluation for drug resistance is highly recommended to determine the success of malaria treatment. 61 The identification of antimalarial drug resistance in Plasmodium species can be performed through several methods, including in vivo, drug level, in vitro, ex vivo, and molecular characterization. 62,63 In 2009, WHO established a protocol to detect antimalarial drug resistance.…”
Section: Detection Of Antimalarial Drug Resistancementioning
confidence: 99%
“…Moreover, sequencing methods are performed using either Sanger or nextgeneration sequencing (NGS), such as Illumina MiSeq, Pyrosequencing, and MinION nanopore, which are suitable to identify numerous genetic markers for antimalarial drug resistance in a large number of samples for each run. 61,[67][68][69] Application of various detection methods in antimalarial drug resistance depends on the facility in malaria endemic areas. In Indonesia, TES is commonly used for the studies of drug resistant, 8,70,71 as well as molecular methods, such as PCR (nested and RFLP).…”
Section: Detection Of Antimalarial Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…[ [31] , [32] , [33] , [34] , [35] ] Although this initiative has impacted and reduced the global burden of the disease, malaria diagnosis, and management in the ICU remain a challenge amidst threats imposed by antimicrobial resistance. [ 19 , 36 , 37 ] This review provides valuable and critical information on the diagnosis and management of malaria in the ICU.…”
Section: Introductionmentioning
confidence: 99%